Strategi Pengembangan Nano Teknologi Dalam Rangka Peningkatan Daya Saing Industri Pertanian Nasional Dengan Menggunakan SWOT-ANP - Nurul Taufiqu Rochman; Gumbira Sa'id; Arief Daryanto; Nunung Nuryartono (Jurnal Ekonomi, 2010)
Nanotechnology is believed to give a significant added value to the agricultural industry. Various applications of nanotechnology provide opportunities for improving the global competitiveness of the agricultural industry. This study aims to assess nanotechnology development strategy at the national agricultural industry by using the quantitative SWOT method and ANP in BOCR (benefit, opportunity, cost, risk) perspective. The results from these two approaches were then compared. There were four stages of the research procedure that consists of 1) analyzing agricultural industries that apply nanotechnology using quantitative SWOT, 2) formulating nanotechnology development strategy in the TOWS matrix quantitatively, 3) determining strategy alternative for developing nanotechnology in the agricultural industry with ANP in BOCR perspective and 4) assessing comparatively weight value of each strategy alternative using quantitative SWOT and ANP in BOCR perspective. Data were collected by conducting FGD (group discussion forum) for 20 participants and a questionnaire to 10 experts in the field of food chemistry, agriculture, nanotechnology and policy. Results show that in the formulation of nanotechnology development strategy on national agriculture industry, aspects of opportunities and positive impact are taken to account more than that risk and economic aspects. ANP results indicate that nanotechnology development in the national agricultural industry is still in the early stage where the strategy that leads to increased mastery of technology is paid more intention than the implementation of research result itself, socialization of nanotechnology safety and governance of policies. Strategy formulation done by ANP in BOCR perspective is slightly different than that done by quantitative SWOT method which uses only independent variables. The result of this study can be used as a reference for stakeholders for strategic decision making in relation to improving the competitiveness of the national agricultural industry through the development of nanotechnology.